CHARACTERISTIC OF APOPTOSIS AND EXPRESSION OF GENES-RELATED APOPTOSIS (c-myc, c-erb AND c-fos ONCOGENE) IN HeLa CELL LINES AFTER EXPOSURE BY NEEM (Azadirachta indica A.Juss) - Arisanty, Dessy; Eshak, Zolkapli; Othman, Fauziah; Rahmat, Asmah; Akim, Abdah M.D.; -, Nurmawaty; M. Jalil, Suhaida. (Universitas Andalas, 2008)
ABSTRACT Azadirachta indica A. Juss is a medicinal plant commonly known as neem. The effect of neem leaves extract on cervical cancer cells, however, has never been studied. Due to the lack of information, this study was conducted to determine the effect of neem leaves extract on cervical cancer (HeLa) cell growth. In vitro cytotoxicity effect of ethanolic neem extract indicated the presence of cytotoxicity activity of the extract against HeLa cells with IC50 of 30.0 μg/mL. The morphological changes under confocal laser scanning microscope (CLSM) on HeLa cells were cell shrinkage and membrane blebbing. There were also cells with condensed nucleus and few cells have fragmented nucleus, and finally formed apoptotic body. Control cells showed a clear cytoplasm and centrally placed nucleus and no cells exhibited any apoptotic features. Appearance of apoptotic cells under scanning electron microscope (SEM) are indentations, blebs and hole on cell surface and disintegration of cell. The controls remained morphologically normal. Apoptotic features of the cells are widely seen with longer incubation time while 24 hours incubation time, it is scarcely seen. The RT-PCR product showed that the c-erb gene expression was expressed in both treated and untreated HeLa cells. Contrary, the the c-myc and c-fos oncogenes on HeLa cells which exposed to A. indica EtOH extract were significantly decreased. Thus, the results from this study strongly suggest that the ethanolic extract of A. indica may contain bioactive compound(s) that caused cervical cancer cells, HeLa cell death by apoptosis mechanism and lead to succession of discovering new alternative treatment for cervical cancer. Keywords : cytotoxic, apoptosis genes, oncogenes, neem